Deconstructing Novice Teachers' Actions and Reactions to Nonharmonic Chilean School Communities of Practice - Gloria Romero (Universidad Nacional de Colombia, 2021)
This paper reports a small section of a larger study that uses a mixed-methods approach to examine participation experiences of novice teachers of English in Chile beginning their careers in nonharmonic public, semiprivate, and private school communities. Drawing on Wenger's framework of communities of practice, this paper reveals that novice teachers come across nonharmonic communities of teachers regardless of the types of schools where they work-that is, schools normally classified by socioeconomic background. As such, new teachers experience varying degrees of challenges that hinder their participation in such school communities. Rather than being a detriment, these nonharmonic communities of practice positively impact novice teachers to strive, including by joining diverse forms of communities, during the first years of teaching.